MECP2 expression in gastric cancer and its correlation with clinical pathological parameters. Issue 31 (August 2017) - Zhang, Jing; Zhao, Junmei; Gao, Ning; Wang, Yanfeng; Chen, Yani; Han, Jiming
Abstract : Abstract: This study is to investigate the expression of methyl CpG binding protein 2 (MECP2) in gastric cancer (GC) and its clinical significance. Expression of MECP2 was analyzed in 69 cases of GC tissues and 12 paracancerous tissues, either by qRT-PCR at the mRNA level or by Western blot and immunochemistry at the protein level. The correlation of MECP2 expression with clinicopathological parameters was analyzed in the 69 GC patients, and validated in data from the TCGA database. The effect of MECP2 expression on survival was also investigated. MECP2 was significantly increased at both mRNA and protein levels in GC compared with paracancerous tissues. MECP2 positive expression was significantly correlated with the TNM stages, histological types, and lymph node metastasis status, but was not correlated with sex or age. Significantly shorter overall survival and disease-free survival was observed in MECP2 positive GC cases compared with the MECP2 negative cases. Univariate and multivariate analyses showed that gender, histological type, lymph node metastasis, and MECP2 expression were independent prognostic factors of GC. The dysregulated expression of MECP2 in GC and its correlation to clinicopathological parameters indicate that MECP2 may regulate the development of GC.